Functional role of cyanidin-3-O-glucoside in osteogenesis: A pilot study based on RNA-seq analysis - Chen, Lin; Hu, Bosen; Wang, Xiaohong; Chen, Yong; Zhou, Bo (Frontiers in Nutrition, 2022)
Cyanidin-3-O-glucoside (C3G) is the most widely distributed anthocyanin and has been shown to reduce the risk of osteoporosis. However, the molecular mechanism by which C3G promotes bone formation is poorly understood. In this study, we performed RNA sequencing (RNA-seq) to clarify the mechanism of action of C3G in osteoblasts. MC3T3-E1 mouse osteoblasts were divided into C3G and control groups, and differentially expressed genes (DEGs) in C3G-treated vs untreated cells were evaluated by RNA-seq analysis. The functions of the DEGs were evaluated by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses, and the genes were validated by quantitative real-time (qRT-)PCR. The RNA-seq analysis identified 34 genes that were upregulated and 17 that were downregulated in C3G-treated cells compared to untreated cells. GO and KEGG pathway analyses showed that these genes were highly enriched in functions related to the lysosome and glycolipid biosynthesis, among others. The differential expression of ATPase H+-transporting V0 subunit C (Atp6v0c), chemokine (C-X3-C motif) ligand 1 (Cx3cl1), and lymphocyte antigen 6 complex, locus A (Ly6a) genes was validated by qRT-PCR; as these genes have been previously implicated in osteroporosis, they are potential target genes of C3G action in ME3T3-E1 cells. These results provide molecular-level evidence for the therapeutic potential of C3G in the treatment of osteoporosis and other disorders of bone metabolism.